Automated minimum-weight sizing design framework for tall self-standing modular buildings subjected to multiple performance constraints under static and dynamic wind loads - Wang, Zixiao; Rajana, Komal; Corfar, Dan-Adrian; Tsavdaridis, Konstantinos Daniel (Engineering structures, 2023)
•The paper contributes to the first ever performance-based,optimisation-driven design routine for reducing the structural material usage in wind-sensitive tall self-standing modular buildings.•The optimisation is relying on a novel discrete sizing formulation considering, concurrently, multiple structural serviceability and safety constraints related to static and dynamic wind loading.•A novel, algorithmically flexible, and computationally efficient solution strategy is devised to solve the above optimisation problem.•The obtained optimal sizing designs can be as cost-effective as conventional building structural systems (in terms of structural steel usage) for tall building applications subjected to moderate wind speed at least.•Providing guidance and recommendations for modular building design through a comprehensive performance assessment of the optimally sized case-study building for different wind intensities. In recent decades, the shortage of affordable housing has become an endemic issue in many cities worldwide due to the ongoing urban population growth. Against this backdrop, volumetric steel modular building systems (MBSs) are becoming an increasingly compelling solution to the above challenge owing to their rapid construction speed and reduced upfront costs. Notwithstanding their success in low- to mid-rise projects, these assembled structures generally rely on a separate lateral load-resisting system (LLRS) for lateral stiffness and resistance to increased wind loads as the building altitude increases. However, additional LLRSs require on-site construction, thereby compromising the productivity boost offered by the MBSs. To this end, this paper proposes a novel optimisation-driven sizing design framework for tall self-standing modular buildings subjected to concurrent drift, floor acceleration, and member strength constraints under static and dynamic wind loads. A computationally efficient solution strategy is devised to facilitate a meaningful sizing solution by decomposing the constrained discrete sizing problem into a convex serviceability limit stage (SLS) and a non-convex ultimate limit stage (ULS), which can be then solved using preferred local and global optimisation methods, separately. The framework is implemented by integrating SAP2000 (for structural analysis) and MATLAB (for optimisation) through SAP2000′s open Application Programming Interface (API), and demonstrated using a 15-storey self-standing steel modular building exposed to three different levels of wind intensity. A comprehensive performance assessment is conducted on the optimally designed case-study building to investigate its elastic instability behaviour, geometric nonlinear effects on wind-induced response, and impacts of global sway imperfections on member utilisation ratios under wind effects. It is concluded that tall self-standing modular buildings can be achieved economically using ordinary corner-supported modules without ad hoc structural provisions, while consuming steel at similar rates to conventional building structural systems. Furthermore, the proposed sizing framework and solution strategy have proven to be useful design tools for reconciling the structural resilience and material efficiency in wind-sensitive self-standing modular buildings.